Cholesterol and oxysterols in retinal neuron-glia interactions: relevance for glaucoma - Masson, Elodie A.Y.; Serrano, Jeanne; Leger-Charnay, Elise; Acar, Niyazi (Frontiers in Ophthalmology, 2024)
Cholesterol is an essential component of cellular membranes, crucial for maintaining their structural and functional integrity. It is especially important for nervous tissues, including the retina, which rely on high amounts of plasma membranes for the transmission of the nervous signal. While cholesterol is by far the most abundant sterol, the retina also contains cholesterol precursors and metabolites, especially oxysterols, which are bioactive molecules. Cholesterol lack or excess is deleterious and some oxysterols are known for their effect on neuron survival. Cholesterol homeostasis must therefore be maintained. Retinal glial cells, especially Müller cells, the principal glial cells of the vertebrate retina, provide mechanical, nutritional, and metabolic support for the neighboring neurons. Several pieces of evidence indicate that Müller cells are major actors of cholesterol homeostasis in the retina, as it is known for other glial cells in the brain. This process is based on a close cooperation with neurons, and sterols can be signaling molecules participating in glia-neuron interactions. While some implication of cholesterol in age-related macular degeneration is now recognized, based on epidemiological and laboratory data, evidence for its role in glaucoma is still scarce. The association between cholesterolemia and glaucoma is controversial, but experimental data suggest that sterols could take part in the pathological processes. It has been demonstrated that Müller glial cells are implicated in the development of glaucoma through an ambivalent reactive retinal gliosis process. The early steps contribute to maintaining retinal homeostasis and favor the survival of ganglion cells, which are targeted during glaucoma. If gliosis persists, dysregulation of the neuroprotective functions, cytotoxic effects of gliotic Müller cells and disruption of glia-neuron interactions lead to an acceleration of ganglion cell death. Sterols could play a role in the glial cell response to glaucomatous injury. This represents an understudied but attractive topic to better understand glaucoma and conceive novel preventive or curative strategies. The present review describes the current knowledge on i) sterol metabolism in retinal glial cells, ii) the potential role of cholesterol in glaucoma, and iii) the possible relationships between cholesterol and oxysterols, glial cells and glaucoma. Focus is put on glia-neuron interactions.